5th ANNUAL ASCOPE LABORATORY TEST CORRELATION PROGAMME ON CFR ENGINE (1983) - Bustani Mustafa; E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1985)
A high precision CFR Engine Laboratory operating according to standard requirement is a must in the oil industry, It is also of very high importance within work of research activities on the use of hydrocarbon fuels. In ASEAN we have the ASCOPE correlation program on CFR engine laboratory to obtain precinion data in the gusoline by CFR test research method.Â Member countries taking part in the 5 laboratory test correlation program for CFR engines are Indonesia as coordinator with six participating laboratories, Malaysia, Philippines, Singupore and Thailand with two laboratories each and USA with are laboratory. The 5th correlation program was started by sending sample by the program correlation in Jamuary, 1983 after being tested the participating laboratories, the test renilt were sent to the program coordinator who procured the result for the determination of standard deviation according to precision and statistics.Â Based on result, conclusion can be drawn about the deviation of laboratory test results.